Lipid accumulation product and visceral adiposity index are associated with dietary patterns in adult Americans. Issue 19 (May 2018) - Mazidi, Mohsen; Gao, Hong-kai; Kengne, Andre Pascal
Abstract : Abstract: In the present study, we aimed to examine the association between lipid accumulation product (LAP) and visceral adiposity index (VAI) with dietary pattern (DP) in the US adults. Participants of the National Health and Nutrition Examination Survey (NHANES) with data available on dietary intake from 2005 to 2010 were included. DPs were derived by principal component analysis. We applied analysis of covariance and multivariable-adjusted linear regressions accounting for the masked variance and utilizing the proposed weighting methodology. The analytical sample comprised 18, 318 participants (mean age = 45.8 years), of whom 48.3% (n = 8607) were men with no age difference by gender ( P = .126). The first DP was representative of a diet rich in carbohydrate and sugar, total fat and saturated fatty acid (SFA), high-caloric dieatry pattern; the second DP was highly loaded with vitamins, minerals and fiber (nutrient-dense dietary patten), and the third DP was mainly representative of high dietary polyunsaturated fatty acids (PUFAs) and monounsaturated fatty acids (MUFAs) (healthy fat DP). The adjusted (age, sex, race, physical activity, smoking, C-reactive protein) mean of LAP, VAI and glucose homeostasis indices increased across increasing quarters of the first DP score (all P < .001), while across increasing score of the second DP, the adjusted mean of LAP, VAI, glucose homeostasis indices decreased (all P < .001). Findings were similar in adjusted linear regressions models. Our findings support that affordable measurements, such as VAI and LAP, could be good alternative surrogate markers of visceral fat. They are also significantly related to DPs in same line as with glucose/insulin homeostasis and anthropometric indices.